Direct antimony recovery from wastewater as anode materials for sodium-ion batteries. (June 2020) - Guo, Lu; Vafakhah, Sareh; Ding, Meng; Pam, Mei Er; Wang, Ye; Shang, Yang; Huang, Shaozhuan; Gu, Chengding; Lim, Yew Von; Yang, Hui Ying
Abstract: The industrial release of antimony (Sb) has caused serious environmental problems and waste of antimony resources in recent years. Herein, we propose a facile approach that can solve these two issues in succession. A promising Sb adsorbent, nitrogen-doped reduced graphene oxide (NGO), was synthesized by a simple hydrothermal method, which further serves as anode materials after Sb adsorption for high-performance sodium-ion batteries. Within 20 min, the as-prepared NGO has demonstrated a high Sb rejection rate of 98% in 500 ppb Sb solution and an exceeding adsorption capacity of 115.57 mg g −1 in 100 ppm Sb solution via effective chemisorption. The chemisorption mechanism has contributed not only to the antimony rejection performance but also the stability of the post-adsorbents. In this way, the post-adsorbent SbOx @NGO was adopted as anode material in sodium-ion batteries. The as-assembled sodium-ion battery exhibits outstanding rate performance and cycling performance with a reversible capacity of 312 mAh g −1 . The work has demonstrated a concept that can reject and recover Sb species simultaneously with minimum pollution and high economical benefit. Highlights: A Sb adsorbent, nitrogen-doped reduced graphene oxide (NGO), was synthesized by a hydrothermal method. The as-prepared NGO has demonstrated a high Sb rejection rate of 98% in 500 ppb Sb solution. The adsorbent based sodium-ion battery exhibits a reversible capacity of 312 mAh g −1 .